Statistical analysis of ionospheric vertical total electron content anomalies before global Mw≥6.0 shallow earthquakes during 2000–2020 - Ma, Yifang; Zhou, Xiaohui; Yang, Yilin; Hu, Leyin; Dong, Hongyan; Yan, Rui (Frontiers in Earth Science, 2023)
The statistical analysis of ionospheric vertical total electron content (VTEC) anomalies before earthquakes can provide potential evidence for the mechanisms of lithosphere-atmosphere-ionosphere coupling. Based on VTEC derived from global ionospheric map (GIM), the statistical analysis of VTEC anomalies occurrence probabilities (Po) and occurrence rates (PE) before 1522 low-depth (≤60 km) strong (Mw≥6.0) earthquakes has been conducted. Different magnitudes, latitudes and focal depths have been considered, and different lengths of sliding windows, equaling 10 days, 15 days and 27 days, respectively, have been utilized. The results show that the significant correlation between Po and epicentral latitudinal locations could be observed within 1-10 days before earthquakes. The values of Po increase with larger magnitudes in the equatorial and low-latitude regions, but decrease with greater magnitudes in the mid- and high-latitude regions to some degree. Within 1-5 days before earthquakes, the overall trend of PE shows an increase with larger magnitudes, but the correlation between the values of PE and magnitudes is relatively weak in the southern mid- and high-latitude regions. There is no evident causality between the occurrence rates of background days (PN) and the magnitude, and most of the values of PE/PN are larger than 1, indicating that VTEC anomalies within a few days before earthquakes are probably related with the forthcoming earthquakes. Moreover, when the abnormal level exceeds 60%, different sliding window lengths have a significant impact on the values of Po and PE in the mid- and high-latitude regions. In particular, there are obvious systematic deviations between the values of Po obtained from different sliding windows in the southern mid- and high-latitude regions.